The Role Of Fınancıal Technology In Improvıng The Economy MSMES On JL. Setıa Budı Medan After Pandemıc Covıd-19 - Chandra Sembiring; Wan Rizca Amelia; Alfifto Alfifto; Siti Alhamra Salqaura; Haryaji Catur Putera Hasman (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study was to determine and analyze the role of financial technology in improving the economy of SMEs on Jl. Setia Budi Medan after COVID-19 pandemic. The data collection technique used in this study was by interview, namely by interviewing several MSME actors on Jl. Setia Budi Medan who uses financial technology such as digital payments and peer to peer lending. Researchers use qualitative research using sources with the collection of samples of SMEs on Jl. Setia Budi Medan. The results of this study can analyze the role of financial technology in helping SMEs on Jl. Setia Budi Medan is improving its economy, which was previously slumped by the COVID-19 pandemic